Beyond “Doing as the Romans Do”: A review of research on countercultural business practices - Caprar, Dan V.; Kim, Sunghoon; Walker, Benjamin W.; Caligiuri, Paula (Journal of International Business Studies, 2022)
Abstract There has long been a dominant logic in the international business literature that multinational corporations should adapt business practices to “fit” host cultures. Business practices that are congruent with local cultural norms have been advocated as effective and desirable, while practices that are incongruent have been deemed problematic. We examine and challenge this persistent assumption by reviewing the literature showing evidence for both benefits and acceptance of countercultural practices (i.e., practices that are seemingly incongruent with local cultural norms or values), and disadvantages and rejection of local practices. Drawing on the literature reviewed, we offer four types of theoretical (ontological, epistemological, causal, and functional) explanations as to why and when countercultural business practices might be preferred. Finally, we provide a springboard for a future research agenda on countercultural practices, centered around understanding the circumstances under which businesses and local stakeholders might benefit from the use of countercultural practices based on such factors as strategic intent, local preferences, institutional drivers, and social responsibility.